Detoxification of AFB1 by Yeasts Isolates from Kefir and Traditional Kefir-Like Products - Abdoljalil Eiri; Hami kaboosi; Farhad Niknejad; Abdollah Ardebili; Hamid Reza joshaghani (Medical Laboratory Journal, 2022)
Background and objectives: Aflatoxin B1 (AFB1) is the most toxic aflatoxin produced by a large number of Aspergillus species. Successful detoxification of this toxin is an important attempt to improve community health. The aim of this study was to evaluate reducing effects of yeasts isolates from kefir and traditional kefir-like fermented beverages on AFB1 in a broth medium. Methods: Polymerase chain reaction-sequencing was carried out to identify the yeast isolates from kefir and kefir-like beverages. Effects of the isolates on AFB1 adsorption and biotransformation in peptone dexterose broth medium were evaluated by using high performance liquid chromatography. Results: Saccharomyces cerevisiae and Kluyveromyces marxianus were isolated from kefir and kefir-like beverages and resulted in 46% and 53% AFB1 adsorption, respectively. The isolates 27Y and 2Y caused 7% toxin biotransformation, while 10% toxin biotransformation was achieved by the isolate 18Y. Conclusion: Our results indicate that the yeast isolates from kefir and traditional kefir-like products can bind to and detoxify AFB1, thereby reducing its harmful effects.